2012
DOI: 10.1200/jco.2012.30.15_suppl.lba7501
|View full text |Cite
|
Sign up to set email alerts
|

TAILOR: Phase III trial comparing erlotinib with docetaxel in the second-line treatment of NSCLC patients with wild-type (wt) EGFR.

Abstract: LBA7501 The full, final text of this abstract will be available at abstract.asco.org at 12:01 AM (EDT) on Monday, June 4, 2012, and in the Annual Meeting Proceedings online supplement to the June 20, 2012, issue of Journal of Clinical Oncology. Onsite at the Meeting, this abstract will be printed in the Monday edition of ASCO Daily News.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…a,b), similar to previous reports comparing TKIs and chemotherapy in pretreated patients . However, a preliminary report from the TAILOR study favored chemotherapy in patients with wt‐ EGFR tumors . The observed higher ORR and the trend toward improved OS in patients with mut‐ EGFR tumors in the erlotinib arm support the predictive value of EGFR mutations for response to TKIs and their use in the first‐line setting .…”
Section: Discussionsupporting
confidence: 84%
“…a,b), similar to previous reports comparing TKIs and chemotherapy in pretreated patients . However, a preliminary report from the TAILOR study favored chemotherapy in patients with wt‐ EGFR tumors . The observed higher ORR and the trend toward improved OS in patients with mut‐ EGFR tumors in the erlotinib arm support the predictive value of EGFR mutations for response to TKIs and their use in the first‐line setting .…”
Section: Discussionsupporting
confidence: 84%
“…OS has not yet been reported for this trial. 89 All three trials comparing second-or third-line therapy with BSC are included in a meta-analysis of published data. 90 The primary analysis was to compare the 1-year survival rate of active therapy with BSC.…”
Section: Targeted Therapy Together With Cytotoxic Chemotherapymentioning
confidence: 99%
“…The co-primary endpoint of the study, non-inferiority of gefitinib compared with docetaxel in OS, was observed [8]. Key trials comparing TKIs to placebo [5,22] and to chemotheraphy [8,[23][24][25] are summarized in Table 2.…”
Section: Egfr Tkismentioning
confidence: 99%
“…Patients with EGFR wildtype NSCLC have a response rate to EGFR TKI therapy of 1%-7%, a median PFS of approximately 2 months, and a median OS of 6 -8 months in retrospective subset analyses of second-line trials [24 -26]. Two recent prospective trials have demonstrated that in the second-line setting, PFS is inferior for patients with EGFR wild-type tumors treated with erlotinib compared with those treated with cytotoxic chemotherapy [25,27]. In one study, OS data are not yet available, and in the other trial, the results were similar between erlotinib and cytotoxic chemotherapy.…”
Section: Second-line Therapy For Patients With Egfr Wild-type Diseasementioning
confidence: 99%